Integrin-Mediated Endothelial Cell Adhesion and Activation of c-Src, EGFR and ErbB2 are Required for Endothelial-Mesenchymal Transition - Arciniegas, Enrique; Carrillo, Luz Marina; Rojas, Héctor; Cardier, José (IntechOpen, 2011)
None